Causal phase in QED3 - Boldo, J. L. [UNESP]; Pimentel, B. M. [UNESP]; Tomazelli, J. L. [UNESP] (Springer Nature, 1997)
The operator S in Fock space which describes the scattering and particle production processes in an external time-dependent electromagnetic potential A can be constructed from the one-particle S-matrix up to a physical phase λ[A]. In this work we determine this phase for QED in (2 + 1) dimensions by means of causality and show that no ultraviolet divergences arise, in contrast to the usual formalism of QED3.